Cable supported bridges concept and design - Gimsing, Niels (John Wiley & Sons, 1997)
Cable supported bridges in the form of suspension bridges and cable-stayed bridges are distinguished by their ability to overcome large spans. This book concentrates on the synthesis of cable supported bridges covering both design and construction aspects. The analytical part covers simple methods to quantify the different structural forms and allows a preliminary optimization of the main structure. Completely revised and updated, this second edition is justified by an accelerated pace of innovation within this field of bridge technology. It includes the latest advancements in wind tunnel testing and results of computer analyses. Numerous halftones and figures supplement the text.